Moisture Redistribution in Full-Scale Wood-Frame Wall Assemblies: Measurements and Engineering Approximation - Charles R. Boardman; Samuel V. Glass; Samuel L. Zelinka (Buildings, 2020)
A counter-balanced mass measurement system was constructed to allow measurement of water loss from a full-scale wood-framed wall assembly. Water was injected onto a localized area of paper towel adjacent to the oriented strand board (OSB) wall sheathing. Moisture pins in the OSB and relative humidity/temperature sensors inside the insulated wall cavity monitored conditions as the wall dried out. The wetted OSB area’s moisture content dropped at a faster rate than the total mass of the wall, indicating moisture redistribution within the wall. A simple model was used to calculate overall moisture redistribution, which was characterized using a near-exponential decay function. This simplification of the inherently three-dimensional physics of moisture redistribution could be incorporated into the one-dimensional hygrothermal models often used in research and engineering practice.